Transformation of Chitinase in Yeast Pichia Pastoris GS115 - Rasyidah, binti Ramlee (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Chitinases are enzyme that degrades chitin, the second most abundant polysaccharide after cellulose. Chitin is found in the exoskeleton of many organisms including insects, fungi, yeast and algae. It is also has been found in the internal structures of other vertebrates. Chitin and the chitinolytic enzymes are very useful for their applications in biotechnology sector. Chitinase contribute in human health care especially in human disease like asthma. Chitinases also have a wide-range application in preparation of pharmaceutically important chitooligosaccharides and N-acetylglucosamin. Transformation of chitinase gene in yeast Pichia pastoris GS115 was performed via EasyCompTM transformation. Chitinase gene extracted from Metroxylan sagu and has been constructed in pPICZαC was used in this project. The confirmation of insertion in the positive transformant that contain pPICZαC/Chitinase vector was done via colony PCR.